2018
DOI: 10.1108/par-11-2016-0098
|View full text |Cite
|
Sign up to set email alerts
|

Related party transactions and finance company failure: New Zealand evidence

Abstract: Purpose This paper aims to examine the existence of related party transactions (RPTs) in failed financial companies in New Zealand when firms have interlocking directors on the board. We also examine the role of auditors in the review of RPTs. We anticipate that inter-company director relationships promote RPTs, while reputable large auditors (i.e. Big4) restrict the practice. Design/methodology/approach This study uses multivariate analysis to examine the determinants of RPTs. We use an unique, hand-collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 53 publications
3
24
0
3
Order By: Relevance
“…A wellconnected board could also be a busy board, as directors can sit on multiple boards and take part in many social events. They appear to spend less time offering advice on strategic innovation initiatives (Bhuiyan & Roudaki, 2018) and do not work as effective monitors (Fich & Shivdasani, 2012). However, Roudaki and Bhuiyan (2015) argued that busy directors are good for the company because they have more diverse knowledge and experience.…”
Section: Directors Network In Technological Innovationmentioning
confidence: 99%
“…A wellconnected board could also be a busy board, as directors can sit on multiple boards and take part in many social events. They appear to spend less time offering advice on strategic innovation initiatives (Bhuiyan & Roudaki, 2018) and do not work as effective monitors (Fich & Shivdasani, 2012). However, Roudaki and Bhuiyan (2015) argued that busy directors are good for the company because they have more diverse knowledge and experience.…”
Section: Directors Network In Technological Innovationmentioning
confidence: 99%
“…Bhuiyan and Roudaki, 2018 [197] The importance of the presence of independent directors as good practice of corporate governance of the company and of the external auditors in the review of related parties transactions.…”
Section: Author/year Main Contributionmentioning
confidence: 99%
“…Francis, 2004;DeFond & Zhang, 2014;Knechel & Shefchik, 2014). In terms of RPTs, several international studies have found that RPTs are at a relatively lower level when companies use Big Four audit firms than when they use other audit firms (and vice versa) (Huyghebaert and Wang, 2012;Bennouri et al, 2015;Cheng et al, 2015;Khan et al, 2016;Habib et al, 2017b;Bhuiyan & Roudaki, 2018).…”
Section: H7: Political Connections Are Positively Associated With Thementioning
confidence: 99%
“…These factors include firm profitability, financial leverage, ownership concentration, CEO-duality, board size, board independence, political connections, and type of audit firm. These factors have been found by several international studies to potentially affect the application of negative RPTs that may harm some investors, especially minority investors (see, for example, Nekhili & Cherif, 2011;Munir et al, 2013;Williams & Taylor, 2013;Kang et al, 2014;Utama & Utama, 2014;Hwang & Wang, 2015;Bava & Di Trana, 2017;Boateng & Huang, 2017;Dicko, 2017;Habib et al, 2017a;Habib et al, 2017b;Bhuiyan & Roudaki, 2018;Habib & Muhammadi, 2018). While a developing country like Jordan may be vulnerable to the negative effects of RPTs, the characteristics of Jordanian companies may have their effect on the degree to which the above-mentioned factors may affect the occurrence of RPTs.…”
Section: Introductionmentioning
confidence: 99%